2002
DOI: 10.1111/1467-9701.00468
|View full text |Cite
|
Sign up to set email alerts
|

The Fallacy of Composition: A Review of the Literature

Abstract: This paper reviews the literature on the fallacy of composition with an emphasis on labour-intensive manufactures. It briefly addresses the protectionist and the partial-equilibrium versions of the argument before focusing on general-equilibrium considerations and the debate on the manufactures terms of trade of developing countries. The review indicates a potential fallacy of composition problem in labour-intensive manufactures, where competition among different groups of developing countries for export marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 19 publications
0
32
0
2
Order By: Relevance
“…5 See Mayer (2003), Kaplinsky (2005) and Razmi and Blecker (2008). 6 The products used include eight metals (aluminum, copper, iron ore, lead, nickel, silver, tin and zinc), seven non-food raw materials (cotton, jute, leather, rubber, timber, tobacco and wool), thirteen food products (rice, maize, wheat, sugar, bananas, soy beans, soy bean oil, palm oil, beef, lamb, swine meat, poultry and fish) and three beverages (cocoa, coffee and tea).…”
Section: Evolution Of the Commodity Terms Of Trade: A First Lookmentioning
confidence: 99%
“…5 See Mayer (2003), Kaplinsky (2005) and Razmi and Blecker (2008). 6 The products used include eight metals (aluminum, copper, iron ore, lead, nickel, silver, tin and zinc), seven non-food raw materials (cotton, jute, leather, rubber, timber, tobacco and wool), thirteen food products (rice, maize, wheat, sugar, bananas, soy beans, soy bean oil, palm oil, beef, lamb, swine meat, poultry and fish) and three beverages (cocoa, coffee and tea).…”
Section: Evolution Of the Commodity Terms Of Trade: A First Lookmentioning
confidence: 99%
“…The literature that empirically tests the fallacy-of-composition hypothesis is relatively small (see the survey in Mayer, 2003). Two of the earliest empirical studies of adding-up constraints were by Cline (1982), who concluded that the rapid export-led growth of the east Asian 'four tigers' (South Korea, Taiwan, Hong Kong, and Singapore) in the 1970s could not plausibly be generalised to a larger set of developing countries without provoking protectionist responses by the industrialised countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Crucial to this vision is the assumption that the growth of reciprocal demand between trading economies creates ever-expanding markets for all countries' exports, so that no country need fear a demand-side constraint on its export growth. In contrast, critics of an export-led growth strategy focused on manufactures have suggested the hypothesis of a 'fallacy of composition', that is, if a number of developing countries simultaneously try to increase their exports in a range of similar products, many of them could end up losing from insufficient foreign demand and possibly depressed international prices (see, for example, Kaplinsky, 1993Kaplinsky, , 1999Blecker, 2002;Mayer, 2003). In this view, the classical liberal vision does not apply because the developing countries sell most of their exports in industrialised country markets, in which case the former countries do not provide the assumed reciprocal demand for each other's exports.…”
Section: Introductionmentioning
confidence: 99%
“…29 Second, is the labor intensity decline of Indian manufacturing production sustainable in an economy with a large amount of idle labor? Third, will the South Asian region be able to catch up the Southeast Asian 29 See Mayer (2003) and the literature therein for a debate on the fallacy of composition argument.…”
Section: Discussionmentioning
confidence: 99%